SOCIAL ANALYSIS OF NARCOTICS ABUSE PREVENTION WOMEN - Andri Winjaya Laksana (UNISSULA, 2019)
Narcotics abuse is a serious problem experienced by various countries including Indonesia. Narcotics abuse can endanger and threaten a Nation. Narcotics problems are not only done by men but also involve women in carrying out their actions both as users and as dealers. The weak position of women in determining policy makes it easy for women to become easy targets in narcotics abuse. The lack of knowledge and understanding related to narcotics and law makes women a powerless element in the chain of narcotics distribution networks. If a woman is trapped in the illicit trafficking of narcotics, it will be feared as an example for her children to follow her actions. This has become a special concern in efforts to tackle Narcotics Crimes carried out by Women.